Forgery of Authentic Deeds by Notaries in The Case of The Judgment of The District Court of Sleman No. 196/PID. B/2018/PN.SMN - Rizky Muthiarani; Siti Hajati Hosein (LEGAL BRIEF, 2022)
As a general officer, a Notary has the authority to make authentic deeds by adhering to the Notary's Rules of Office and Ethics. However, in practice, Notaries still abuse their power in doing original deeds, namely without following the obligations and limitations set in the laws and regulations and even forging letters. This can cause adverse legal consequences for related parties and Third Parties. If this happens, the Notary can be blamed and asked for compensation by parties who feel aggrieved and cause implications in the form of Notary responsibility. This research will focus on discussions related to the authority to make Notarial deeds and the responsibility of Notaries if they are proven to have committed criminal acts of forgery of authentic deeds. This research will also discuss the legal consequences imposed on Notaries by analyzing the Sleman District Court Decision Number 196 / Pid.B / 2018 / PN.Smn. The research method used is a juridical-normative approach, examining the principles and elements of the Notary Position and Ethics Regulations and the Criminal Code. The results of this study show that the validity of a deed made by a Notary without meeting formal requirements or material requirements is null and void and is considered to have never been born. A copy of the deed issued is an act of forgery of letters. The consequences for a Notary who is proven to have committed the show can be in the form of administrative sanctions and can be threatened with criminal sanctions based on the provisions of Article 264 paragraph (1) of the Criminal Code.